Mutation of Drosophila focal adhesion kinase induces bang-sensitive behavior and disrupts glial function, axonal conduction and synaptic transmission. - Ueda, A.; Grabbe, C.; Lee, J.; Lee, J.; Palmer, R.H.; Wu, C.F. (European Journal of Neuroscience, 2008)
The role of the conserved focal adhesion kinase (FAK) family of protein tyrosine kinases in the development and physiological functions of the CNS has long been an area of interest among neuroscientists. In this report, we observe that Drosophila mutants lacking Fak56 exhibit a decreased lifespan, accompanied by a bang-sensitive phenotype, which is characterized by sensitivity to mechanical and high-frequency electrical stimulation. Fak56 mutant animals display lower thresholds and higher rates of seizures in response to electroconvulsive stimuli. Direct measurements of action potential conduction in larval segmental nerves demonstrate a slowed propagation speed and failure during high-frequency nerve stimulation. In addition, neuromuscular junctions in Fak56 mutant animals display transmission blockade during high-frequency activity as a result of action potential failure. Endogenous Fak56 protein is abundant in glial cells ensheathing the axon bundles, and structural alterations of segmental nerve bundles can be observed in mutants. Manipulation of Fak56 function specifically in glial cells also disrupts action potential conduction and neurotransmission, suggesting a glial component in the Fak56 bang-sensitive phenotype. Furthermore, we show that increased intracellular calcium levels result in the dephosphorylation of endogenous Fak56 protein in Drosophila cell lines, in parallel with our observations of highly variable synaptic potentials at a higher Ca2+ level in Fak56 mutant larvae. Together these findings suggest that modulation of Fak56 function is important for action potential propagation and Ca2+-regulated neuromuscular transmission in vivo.